HEDGING AND POLITENESS STRATEGIES IN CONTEMPORARY DIPLOMATIC DISCOURSE: A CORPUS-BASED ANALYSIS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Diplomatic language functions as a highly specialized register in which linguistic choices are calibrated to manage interpersonal and inter-state relations under conditions of potential conflict. This study suggests that hedging devices and politeness strategies serve as central mechanisms for mitigating face-threatening acts (FTAs), preserving strategic ambiguity, and facilitating the maintenance of international cooperation. Drawing primarily on Brown and Levinson’s (1987) politeness theory, supplemented by insights from pragmatics and elements of speech act theory, the present research examines a corpus of 15 authentic English-language diplomatic texts (approximately 45,000 words) drawn from UN General Assembly speeches and foreign ministry statements issued between 2022 and 2025.